What Is Worth Conserving? - Vella, John M. (Modern Age)
The article presents information on the gradual disappearance of some journals of opinion in the U.S. and Great Britain. In 1955, Russell Kirk attempted to explain the disappearance in the periodical "Commonweal." According to Kirk, the reasons for this trend were the economic conditions and the material sacrifices needed to fight the two world wars. Kirk says that the best elements of American and European thought should be conserved.